2008
DOI: 10.1017/s026646230808029x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing short-term effects and costs at an early stage of innovation: The use of positron emission tomography on radiotherapy treatment decision making

Abstract: The use of PET for radiotherapy decision making seems more valuable for lung cancer than for Hodgkin's disease, both in terms of costs and changes in radiotherapy treatment. This result might help policy makers for prioritization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In general, when analyzing the marginal costs, the results indicate a disadvantage of HC when compared to hospital care units. These results can be observed in the studies by Fuente [16] and Remonnay et al [20]. It should be considered that marginal cost involves the addition of total production costs when the quantity produced per unit is increased, since this cost involves the supply (or withholding) of an additional unit of the service or practice analyzed.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In general, when analyzing the marginal costs, the results indicate a disadvantage of HC when compared to hospital care units. These results can be observed in the studies by Fuente [16] and Remonnay et al [20]. It should be considered that marginal cost involves the addition of total production costs when the quantity produced per unit is increased, since this cost involves the supply (or withholding) of an additional unit of the service or practice analyzed.…”
Section: Discussionsupporting
confidence: 62%
“…According to the results, HC has an increasing marginal variation, i.e., the cost increases as the quantity produced increases. The study by Remonnay et al [20] showed that this increase was due to the much higher cost of staff and medication at home. However, the nal average cost of home intervention was lower, which is due to the noninclusion of overhead costs, which was $120.30 (in the hospital) and $20.10 (at home).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interobserver variability in delineating tumor volumes was diminished when 18 F-FDG PET was used for planning [38]. In addition to its enhanced clinical value in radiotherapy planning, the use of 18 F-FDG PET/CT altered the therapeutic strategy in 40 % of patients with NSCLC, which resulted in an overall cost reduction for treatment in this group [39].…”
Section: Radiotherapy Planningmentioning
confidence: 99%
“…Therefore the number of performed procedures recorded during both data acquisition periods was above such break even point [7]. However, given the value in public health of PET/CT and the amount of the initial investment, the importance of executing the maximum possible number of exams is clear [8,9].…”
Section: Discussionmentioning
confidence: 99%